Can natural scenes cue attention to multiple locations? Evidence from eye-movements in contextual cueing - Albert, Josefine; Schneider, Werner X.; Poth, Christian H. (Frontiers in Cognition, 2024)
Humans find visual targets faster when the target appears at the same location in a repeated configuration of other stimuli. However, when the target alternates between two locations in the repeated configuration, the benefit for visual search is smaller. This reduction of benefits has been explained as an averaging of the benefits for one and costs for the other location(s). In two experiments, we investigated this two-target-locations effect in real-world scenes with high-resolution eye tracking. Experiment 1 adapted a study where subjects searched for a small "T" or "L" superimposed on real-world photographs. Half of the trials showed repeated scenes with one possible target location each, half showed novel scenes. We replicated the pronounced contextual cueing effect in real-world scenes. In Experiment 2, two conditions were added. In one of them, targets appeared in repeated scenes alternating between two possible locations per scene. In the other condition, targets appeared in repeated scenes but at new locations constrained to one screen side. Subjects were faster to search and discriminate a target in repeated than in novel scenes, also when the scene was paired with two alternating target locations and (after extensive training) even when the scene only predicted the hemifield. Separate analyses on the two possible target locations rejected the suggestion of costs for the additional target location, since for both the favored and less favored target location, the contextual cueing effect was present in the experiment’s second half. The eye tracking data demonstrated that contextual cueing influences searching fixations, characteristic of attentional guidance, rather than responding fixations, characteristic of facilitation of response processes. Further, it revealed that adding another possible target location leads to a lesser amount of guidance rather than impediment of response processes. Thus, this study delivers evidence for a flexible and attentional guidance mechanism that is able to prioritize more than one location in natural contexts.